Investigating serumic levels of antibodies against Mycobacterium avium supspecies paratuberculosis using the ELISA method in Holstein dairy cattle - yavar heydarzadeh Asiabi; Behboud Jafari; Ali hassanpour (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2018)
Paratuberculosis (Johne’s disease) is achronic bacterial infection of ruminants causing body wasting due to severe and protracted diarrhea. The aim of the present study was to investigate the rate of infection to Johne’s disease in cattle of Moghan agro-business and animal husbandry complex by detecting antibody titers against Mycobacterium avium subspecies paratuberculosis (MAP) using the absorptive ELISA method. For this purpose, blood samples were collected from 738 randomly selected milking cattle of Moghan agro-business and animal husbandry complex and their sera were assessed by ELISA method. The results indicated that 58 cattle had antibody titers against MAP with S/P percentage over 60% (infection rate of 7.86%) of which 25 cattle were positive (with S/P percentage over 70%) and 33 were suspicious (with S/P percentage between 60-70%). Because Johne’s disease is manifested as a subclinical disease and infected cattle seem to be apparently healthy, bacteria are shed through faeces and body secretions causing infection of the rest of the herd. Thus performing periodic herd screening tests and testing recently introduced animals alongside other preventive measures is strictly advised.